Turk dostu bhopal emiri Siddik Hassan hana'in arap dilineki yeri - Arn , Ali Junayt; Jassim, Layeth Suud (University of At-Tarturk, Arzrum, Turkey, 2002)
In this study, Bhopal Emeer and commentator on the Qur'an Sıddık Hasan Khan's historical life and his situation in the Arabic Language and Literature and his influence for afier him has been discussed.